PENGARUH KOMITMEN ORGANISASIONAL, PENGEMBANGAN KARIER, MOTIVASI KERJA DAN KARAKTERISTIK INDIVIDUAL TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PEMERINTAH KABUPATEN HALMAHERA TIMUR - Djamaludin, Musa (Program Doktor Ilmu Ekonomi, 2009)
Along with the forming of East Halmahera Regency at 2003, development activities develop rapidly. One of several determining factors of development success is determined by nation apparatus resource. The number of PNS that become the population in this research are employees in the Capital of East Halmahera Regency that isMabaCitywhich total population is 617 persons. Human resources management influences organizational performance by increasing employee’s commitment that supported by good behavior of all employees. When each employee has commitment, good individual characteristics and good motivation, every employee is hopefully will be able to get working satisfaction and then, these satisfied employee will be able to increase their performance. In this research, there is 200 employees or 31,32 percent (200/617 x 100%) from the whole population. However, the fact in the field shows that the number of questionnaire as the result of respondents’ answer cannot be tabulated completely, because there is only 194 questionnaire that considered appropriate. It is because 6 of them are destroyed and cannot be interpreted. Sample collection is done by using proportional stratified random sampling technique. Relation among variables in this research is analyzed with SEM (Structural Equation Modeling) with AMOS 4.01 program. The result of examination to Goodness of Fit Index (GFI) criteria after model is modified shows that confirmatory analysis and structural Equation Modeling in this research can be accepted because of model fit with Chi-square score = 164.94 (critical value < 124.34); GFI = 0,924 (critical value > 0,90); and AGFI = 0,841 (critical value > 0,90). From the result of this research model, it is found out that organizational commitment, career development and work motivation is effective enough when it is used as stimulator of jobb satisfaction and employee’s performance. In other words, work satisfaction and employee’s performance can be improved through organizational commitment, career development; work motivation and individual characteristics. Among organization commitment, career development, work motivation and individual characteristic variables in the forming of jobb satisfaction and employee’s performance, individual characteristic gives the lowest contribution. It shows that individual characteristic is a factor that needs to receive better attention in order to support employee working achievement. Keywords: organizational commitment, career development, work motivation, individual characteristics, job satisfaction, employee performance, East Halmahera Regency.